2019
DOI: 10.1166/nnl.2019.3011
|View full text |Cite
|
Sign up to set email alerts
|

H2S Gas Sensor Based on WO3 Nanostructures Synthesized via Aerosol Assisted Chemical Vapor Deposition Technique

Abstract: Herein we demonstrate tungsten oxide (WO3 nanostructures based resistive type sensors for hydrogen sulfide (H2S) gas sensing utility. The WO3 dynamic layers have been deposited upon alumina substrates pre-patterned with gold (Au) interdigitated electrodes. For comparative study, two distinct WO3 nanostructures (S-425 and S-450) have been synthesized using Aerosol Assisted Chemical Vapor Deposition (AACVD) technique at varied deposition temperatures i.e., 425 and 450 °C, respectively. The gas detecting propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Recent advances in nanostructure-based sensor system have been widely reported. Co-MoS 2 nanomaterials on carbon electrode was fabricated for 4-aminophenol sensor, 29 WO 3 nanostructures was synthesized to detect H 2 S gas, 30 and two-dimensional MXene were used for solar energy harvesting. 31 The large-scale transfer of these various nanostructures will be included in future studies using our roll-to-roll UV lamination process.…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in nanostructure-based sensor system have been widely reported. Co-MoS 2 nanomaterials on carbon electrode was fabricated for 4-aminophenol sensor, 29 WO 3 nanostructures was synthesized to detect H 2 S gas, 30 and two-dimensional MXene were used for solar energy harvesting. 31 The large-scale transfer of these various nanostructures will be included in future studies using our roll-to-roll UV lamination process.…”
Section: Resultsmentioning
confidence: 99%
“…The findings highlighted the significant impact of deposition temperature on the sensing performance, with the S-450 sensor exhibiting superior sensitivity due to its improved crystallinity and surface morphology. 100 Two different WO 3 nanostructures, S-425 and S-450, were synthesized at deposition temperatures of 425 °C and 450 °C, respectively. The gas sensing properties of these sensors were investigated by exposing them to varying concentrations of H 2 S gas (0-60 ppm) at a low operating temperature of 250 °C and a DC bias of 5 V. The results showed that as the concentration of H 2 S gas increased from 0 to 10 ppm, the average resistance of the S-425 and S-450 gas sensors decreased by 96.5% and 97.6%, respectively.…”
Section: Fabrication Techniques For Mos-based E-nose Systemsmentioning
confidence: 99%
“…The significantly enhanced sensing performance of the S-450 sensor was due to its improved crystallinity and surface morphology, which enhanced the adsorption/desorption kinetics of ions. 100 AACVD can also be used to create interstitial defects in MOS, which enhance the gas sensing performance of MOSbased sensors. 95,98 ZnO films with nanoparticulate and nanopyramidal structures exhibited favorable gas responses to NO 2 gas.…”
Section: Fabrication Techniques For Mos-based E-nose Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, some classical metal oxide semiconductor (MOS) nanomaterials exhibit low cost, easy fabrication, high sensitivity, fast response, portability, and other benign characteristics, thus having potential applications in TEA measurement. Among those, In 2 O 3 , a typical n-type semiconductor with a wide band gap (a direct gap of 3.5–3.7 eV), has excellent conductivity and superior photoelectrochemical stability to pave the way for gas sensors. , Besides, the uniformity, morphology, and constitution of materials are known to have great effects on their sensing performances; therefore, various In 2 O 3 products with modified morphology or tunable components have been fabricated, especially, these In 2 O 3 nano/microstructures have manifested good sensing performance to CO, ethanol, formaldehyde, acetone, etc. Comparatively, it is a rare report on the safety detection of TEA by In 2 O 3 -based nanocomposites, not to mention the single phase of In 2 O 3 with highly efficient sensing performances and lower working temperatures. Based on these requirements, so far, we have not found many reports.…”
Section: Introductionmentioning
confidence: 99%